Novel chemical synthetic route and characterization of zinc selenide thin films - Hankare, P. P.; Chate, P. A.; Delekar, S. D.; Asabe, M. R.; Mulla, Imtiaz S. (Journal of Physics and Chemistry of Solid, 2006)
Zinc selenide (ZnSe) thin film have been deposited using chemical bath method on non-conducting glass substrate in a tartarate bath containing zinc sulfate, ammonia, hydrazine hydrate, sodium selenosulfate in an aqueous alkaline medium at 333 K. The deposition parameter of the ZnSe thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption, electrical measurements, atomic absorption spectroscopy (AAS). The ZnSe thin layers grown with polycrystalline zinc blende system along with some amorphous phase present in ZnSe film. The direct optical band gap `E-g' for the film was found to be 2.81 eV and electrical conductivity in the order of 10(-8)(Omega cm)(-1) with n-type conduction mechanism. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: chalcogenides; electronic materials

New route for preparation of luminescent mercaptoethanoate capped cadmium selenide quantum dots - Wankhede, Manoj E.; Inamdar, Shaukatali N.; Deshpande, Aparna; Thete, Aniket R.; Pasricha, Renu; Kulkarni, Sulabha K.; Harani, Santosh K. (Bulletin of Materials Science, 2008)
We report a synthesis of cadmium selenide quantum dots (Q-CdSe) by refluxing a mixture of cadmium acetate, selenium powder, sodium sulfite and 2-mercaptoethanol in N,N'-dimethyl formamide (DMF)/water solution. X-ray and electron diffractions suggest the formation of hexagonal phase of size quantized CdSe. Based on TEM analysis, the formation of nanoparticles with an average diameter of 3.5 +/- 0.5 nm is inferred. Their sols in DMF and dimethyl sulphoxide (DMSO) gave characteristic absorption peaks at 300 nm and 327 nm, which is attributed to the formation of high quality, size quantized CdSe particles. Extracted particles from the sol were readily redispersed in DMF and DMSO, which were diluted further with water without losing their optical and colloidal properties. FTIR spectroscopy suggested the formation of 2-mercaptoethanol thiolate on the particle surface, with free -OH groups available for linkage. Sols in DMSO and their solutions in water displayed an intense photoluminescence (PL).
Keywords: chalcogenides; Chemical synthesis; photoluminescence; semiconductor quantum dots

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Electrochemical evaluation of the stability and capacity of r-GO-wrapped copper antimony chalcogenide anode for Li-ion battery - Yadav, Poonam; Sharma, Neha; Patrike, Apurva; Sabri, Ylias M.; Jones, Lathe A.; Shelke, V. Manjusha (ChemElectroChem, 2020)
Poor cycling stability and capacity fade are primary concerns for next-generation anode materials for Li-ion batteries. In non-carbonaceous anode materials, alloying with Li leads to volume increase that affects practical applications, and increase in particle size, amorphization and reduced conductivity can all lead to a loss of performance. In this work, binary antimony sulfide (Sb2S3) and ternary copper antimony sulfide (CuSbS2) are synthesized by a convenient solvothermal process. These materials are used to study the Li-active/inactive concept, by incorporating Cu into Sb(2)S(3)forming CuSbS(2)wherein Cu is Li inactive whereas Sb is Li active. By direct comparison, we have shown that incorporating Cu into binary antimony sulfide (Sb2S3) resulting into ternary copper antimony sulfide (CuSbS2) addresses the problem of poor conductivity and capacity loss, as Cu provides conductivity leading to enhanced charge transfer and prevents Sb particle aggregation while charge-discharge by exhibiting spectator or diluent ion effect. The better performance of CuSbS(2)is associated with the better Li(+)ion diffusion in the CuSbS2(D=8.97x10(-15) cm(2) s(-1)) compared to Sb2S3(D=2.76x10(-15) cm(2) s(-1)) and lower series resistance of CuSbS2(R=4.70x10(5) omega) compared to Sb2S3(R=5.81x10(8) omega). We have also investigated the composite with the addition of rGO. The CuSbS2-rGO delivered a reversible capacity of 672 mAh g(-1)after 1000 cycles at 200 mA g(-1)which has shown best performance.
Keywords: Batteries; chalcogenides; Diffusion coefficient; lithium; Ternary sulfides